PERSEPSI PENGGUNA JALAN TERHADAP FASILITAS PEJALAN KAKI DI KAWASAN JALAN PEMUDA KOTA SEMARANG - Nusadhani, Prananing; Mudiyono, Rachmat; Poedjiastoeti, Hermin (Pondasi, 2024)
This study aims to analyze road users' perceptions of pedestrian facilities in the Pemuda Corridor (Lawang Sewu – Mall Paragon), Semarang City. Variables such as safety, comfort, accessibility, and infrastructure quality are the focus of this research. Data were collected through questionnaires with a sample of 400 people, field observations, and interviews. Field study results indicate that despite many positive aspects of the current pedestrian pathways in the Pemuda Corridor, there are still deficiencies that need improvement. Certain areas require additional zebra crossings and traffic lights to enhance safety. Furthermore, cleanliness and maintenance of the sidewalks in some spots are still suboptimal. Accessibility for people with disabilities also needs enhancement, as there are still obstacles such as vehicles and vendors occupying the pedestrian paths. The physical condition of the pedestrian pathways is generally good, but some areas require upgrades. These findings imply the need for municipal government intervention to improve the safety, comfort, and accessibility of pedestrian pathways through the addition of safety facilities, stricter enforcement of regulations, and regular maintenance programs. Involving the local community in the planning and management process of pedestrian pathways is also recommended to identify problems more effectively and develop solutions that meet community needs. With these steps, it is expected that pedestrian facilities in the Pemuda Corridor and other areas in Semarang City can be improved to create a safer, more comfortable, and inclusive environment for all pedestrians.